MANAJEMEN PENDIDIKAN YANG INKLUSIF: MENYUSUN KEBIJAKAN UNTUK PENDIDIKAN YANG SETARA DAN BERKUALITAS (Inclusive Education Management: Formulating Policies for Equitable and Quality Education) - Ayu Mawarmi Asriyanti; Iplah Muhlisin; Tiara Puspita sari; Yunita Silvi; Sukatin Sukatin (JURNAL ILMIAH RESEARCH AND DEVELOPMENT STUDENT, 2025)
Inclusive education refers to an educational approach that provides equal opportunities for all students, regardless of their socio-economic background, ability, or disability. This paper explores the concept of inclusive education management, with a focus on formulating policies that promote equitable access to quality education. By examining key strategies and international best practices, this paper outlines how educational systems can develop and implement policies that foster inclusivity, ensuring that all learners can succeed in an environment that values diversity.